PROBLEMS FACING AGRICULTURAL EXTENSION SERVICE PROVIDERS TO FACE THE EFFECTS OF CLIMATE CHANGE IN BAGHDAD GOVERNORATE : PROBLEMS FACING AGRICULTURAL EXTENSION SERVICE PROVIDERS TO FACE THE EFFECTS OF CLIMATE CHANGE IN BAGHDAD GOVERNORATE (Iraqi Journal of Market Research and Consumer Protection, 2024)
The research aimed to determine the problems facing agricultural extension service providers to face the effects of climate change, the research community included all workers in the provision of agricultural extension service in the province of Baghdad and distributed to the Department of Agriculture of Baghdad Karkh and agricultural divisions affiliated to it and the Department of Agricultural Extension and Training in the province of Baghdad, the number of (110) individuals. All members of the community were taken as a sample for research due to their small number. To achieve the objectives of the research, a questionnaire was prepared to collect data from the respondents, consisting of (28) items distributed in three areas (problems concerned to farmers, problems concerned to agricultural extension service providers themselves, problems concerned to coordination and government support). The results of the research showed that there are several problems that hinder the workflow of service providers' agricultural extension services in providing their extension services to farmers in the field of facing the effects of climate changes in varying degrees, as the problem of the lack of specialists in agricultural extension in the field of climate changes came in the first place in terms of importance, which got a weighted mean of (3.68) degrees and a weight percentile of (92%), While the problem of extension service providers not having the skills and knowledge in determining the best agricultural practices to face climate change came in the last place in terms of importance, which got a weighted mean of (3.13) degrees with a weight percentile of (78.25%). The researcher recommended the necessity of adopting the research findings regarding the problems faced by agricultural counseling service providers and working on resolving them through the development of a training and educational plan to enhance their skills and capacities in dealing with agricultural challenges associated with climate change. Additionally, it emphasized the importance of governments and financial institutions providing financial and moral support to enhance their ability to deliver effective agricultural counseling services and assist them in tackling the challenges and problems they encounter.